Educação, família e escola: estudo em uma escola de Miranorte-TO - Silva, Aline Luana da (Universidade Federal do Tocantins, 2023)
The object that guided this research arose from the interest in analyzing the legal instruments that govern Brazilian education in the scope of the articulation between school and family and the integration actions family/school developed by the school. Thus, realizing the importance of the family-school relationship and the family's participation in the school environment for the children's school performance. The central question of the research is to seek answers to which actions were being developed by a school in Miranorte - TO to promote the family approach? Thus, in our first section we talked about the concepts of education, school and family, also bringing a brief history about the beginning of the educational process of education in Brazil. Next, we present the concept of family and the legal mechanisms to guarantee its rights. In the third section, a brief characterization of the place where the research was carried out, the methodological procedures, in addition to the results and discussions.Thus, in the methodology we resorted to the qualitative research method, accompanied by bibliographic and field research to reflect on the importance and appreciation of the family-school relationship in the educational process of the child, as a way to enable the child's development and to broaden his/her learning process.